Oral Presentation No. 41 High plasma von Willebrand factor concentration is associated with the development of bleeding complications in patients with polyvascular disease receiving multicomponent antithrombotic therapy. (21st October 2022) - Krivosheeva, E; Komarov, A; Dobrovolsky, A; Korobkova, V; Titaeva, E; Tripoten, M; Balakhonova, T; Panchenko, E
Abstract: Background: von Willebrand factor (VWF) is well known biochemical marker of endothelial dysfunction that increased may be associated with the development of thrombotic complications in patients with polyvascular disease (PD). We aimed to asses the relation of VWF to the development of bleeding outcomes in patients with PD receiving multicomponent antithrombotic therapy (MAT). Material and methods: The data were obtained during the prospective register REGATA-1, NCT04347200. 95 patients (70 males), median age 67 [IQR 61; 72] with PD (coronary artery disease and peripheral atherosclerosis of at least one vascular territory ≥ 50%) were enrolled. 61% of patients received acetylsalicylic acid in combination with rivaroxaban 2.5 mg bid, other (39%)with clopidogrel. Median follow-up was 10 months [IQR 8.0; 12.0]. The safety end point was major and clinically relevant bleedings (type 2–5) according to the BARC classification. Plasma samples for VWF were taken at the inclusion and analyzed using ELISA. Results: Frequency of BARC 2–5 bleedings was 20%. The most frequent (79%) was gastrointestinal bleedings. Median VWF plasma concentration was 154% [116; 196]. According to the quartile analysis, VWF values in the top three quartiles distribution (cut-off value > 122%) were associated with a higher frequency of bleeding events: 3.7% versus 36.7%, OR 8.8; CI 1, 11-69, 9, ? = 0.0392. Bleeding-free survival in groups formed depending on the VFW plasma concentration (122 > and ≤ 122%) was 96.2% vs. 73.9%, respectively, Log-Rank P = 0.0488. Conclusions: Increase of VWF plasma concentration (> 122%) is associated with the development of major and clinically relevant bleedings in patients with PD receiving MAT.